Otimização da localização de Unidades de Saúde da Família do município de João Pessoa - Silva, Ingrid Bergmam do Nascimento (2021)
Over the past few years, with the support of the Ministry of Health (MS), an expansion of the Family Health Strategy (ESF) has taken place. The ESF is seen as a priority strategy for Primary Care (BA), as well as the gateway to the Unified Health System. The objective was to propose locations for relocation of Family Health Units, in order to optimize (maximize) the care provided to the population of the city of João Pessoa-PB. This is a quantitative study of geographic space planning in which a problem of location of facilities will be solved, the facilities also called facilities, in this work are the Family Health Units, and the demand is the population of the municipality of João Pessoa. The model used was the Maximum Coverage Location Model. Data relating to the USFs, their locations and whether the buildings where they operate are owned by the municipality of João Pessoa or rented, were obtained from public agencies: Municipal Health Department of the Municipality of João Pessoa, as well as from the National Register of Establishments of Health (CNES). The addresses of all Family Health Units in the city of João Pessoa were collected. The geolocation files for the municipality of João Pessoa were obtained from IBGE (shape file). R Software and ArcGIS were used. The study was carried out in three stages: first, an analysis was made in relation to the current location of the Family Health Units (USF) currently operating in the city of João Pessoa and the coverage produced by them. In the second stage, an analysis of the leased USFs (which were the only ones considered to be subject to relocation) was carried out in order to verify which ones were really contributing to the best coverage. In the third stage, an analysis of the neighborhoods was carried out to identify which ones had the greatest lag of USFs in terms of distance between the centroids of their census sectors and USFs. After this step, different approaches were suggested to assist in the decision-making process for the relocation of the 8 leased USFs that were not contributing to the coverage. Aiming in this way to facilitate the access of users to these services, reducing the distance between the individual's residence and the health service. Since there are several approaches to the decision-making process, we propose some suggestions for approaches to support decision-making by managers. The first approach would be to allocate USFs rented in neighborhoods with more discovered centroids, namely: Manaíra, Bessa, Miramar, Valentina, Gramame, Bancários, Paratibe and Portal do Sol. further away, namely: Paratibe, Mussure, Alto do Céu, Valentina, Manaíra, Bairro das Indústrias, Mangabeira and Bessa. A third suggestion would be to relocate leased USFs to densely populated neighborhoods. And yet a fourth suggested approach would be to relocate leased USFs to more populous neighborhoods. With this, it was possible to propose locations for relocation of Family Health Units in the city of João Pessoa, where units that operate in rented buildings were preferred. The approach adopted showed potential to optimize the locations of the Family Health Units, the identification of adjustment of these locations can help in the relocation of USFs already in operation, as well as new units that will be installed in the city of João Pessoa in the neighborhoods that more need, aiming to collaborate in filling possible gaps in planning and assist the management of Primary Care in the municipality, as well as serving as a subsidy for managers in the decision-making process in health.